CHADS2 Scores in the Prediction of Major Adverse Cardiovascular Events in Patients with Cushing’s Syndrome - Yuh-Feng Wang; Mei-Hua Chuang; Tzyy-Ling Chuang; Kung-Yung Huang; Shaw-Ruey Lyu; Chih-Yuan Huang; Ching-Chih Lee (International Journal of Endocrinology)
Vascular events are one of the major causes of death in case of Cushing’s syndrome (CS). However, due to the relative low frequency of CS, it is hard to perform a risk assessment for these events. As represented congestive heart failure (C), hypertension (H), age (A), diabetes (D), and stroke (S), the CHADS2 score is now accepted to classify the risk of major adverse cardiovascular events (MACEs) in patients with atrial fibrillation. In this study, participants were enrolled from the National Health Research Institute Database (NHIRD) of Taiwan, and we reviewed 551 patients with their sequential clinically diagnosed CS data between 2002 and 2009 in relation to MACEs risk using CHADS2 score. Good correlation could be identified between the CS and CHADS2 score (AUC=0.795). Our results show that patients with CS show significantly higher risk of vascular events and the CHADS2 score could be applied for MACEs evaluation. Adequate lifestyle modifications and aggressive cardiovascular risks treatment are suggested for CS patients with higher CHADS2 score.